Gold nanoparticles stabilized with sulphonated imidazolium salts in water and reverse micelles. Issue 7 (19th July 2017) - Monti, Gustavo A.; Fernández, Gabriela A.; Correa, N. Mariano; Falcone, R. Darío; Moyano, Fernando; Silbestri, Gustavo F.
Abstract : Herein we describe the synthesis of gold nanoparticles (Au-NPs) in presence of sulphonated imidazolium salts [1, 3-bis(2, 6-diisopropyl-4-sodiumsulfonatophenyl)imidazolium (L1 ), 1-mesityl-3-(3-sulfonatopropyl)imidazolium (L2 ) and 1-(3-sulfonatopropyl)imidazolium (L3 )] in water and in a confinement environment created by reverse micelles (RMs). The Au-NPs were characterized—with an excellent agreement between different techniques—by UV-vis spectroscopy, transmission electron microscopy (TEM), dynamic light scattering (DLS) and zeta potential. In homogeneous media, the Au-NPs interact with the imidazolium ring and the sulphonate groups were directed away from the NPs' surface. This fact is responsible for the Au-NPs' stability—over three months—in water. Based on the obtained zeta potential values we assume the degree of coverage of the Au-NPs by the imidazolium salts. In n -heptane/sodium 1, 4-bis (2-ethylhexyl) sulfosuccinate (AOT)/water RMs, the Au-NPs formed in presence of sulphonated imidazolium salts present different patterns depending on the ligand used as stabilizer. Interestingly, the Au-NPs are more stable in time when the salts are present in AOT RMs (three weeks) in comparison with the same RMs system but in absence of ligands (less than an hour). Clearly, the sulphonated imidazolium salts are very effective Au-NPs stabilizers in a different medium and this generates a plus to be able to use them for multiple purposes.